Diffusion tensor imaging in anterior interosseous nerve syndrome - functional MR Neurography on a fascicular level - Godel, Tim; Kronlage, Moritz; Schwarz, Daniel; Heiland, Sabine; Bendszus, Martin; Bäumer, Philipp (NeuroImage: Clinical, 2019)
Purpose - By applying diffusor tensor imaging (DTI) in patients with anterior interosseous nerve syndrome (AINS), this proof of principle study aims to quantify the extent of structural damage of a peripheral nerve at the anatomical level of individual fascicles. - Methods - In this institutional review board approved prospective study 13 patients with spontaneous AINS were examined at 3Tesla including a transversal T2-weighted turbo-spin-echo and a spin-echo echo-planar-imaging pulse sequence of the upper arm level. Calculations of quantitative DTI parameters including fractional anisotropy (FA), mean diffusivity (MD), radial diffusivity (RD), and axial diffusivity (AD) for median nerve lesion and non-lesion fascicles as well as ulnar and radial nerve were obtained. DTI values were compared to each other and to a previously published dataset of 58 healthy controls using one-way Analysis of Variance with Bonferroni correction and p-values <.05 were considered significant. Receiver operating characteristic (ROC) curves were performed to assess diagnostic accuracy. - Results - FA of median nerve lesion fascicles was decreased compared to median nerve non-lesion fascicles, ulnar nerve and radial nerve while MD, RD, and AD was increased (p<.001 for all parameters). Compared to median nerve values of healthy controls, lesion fascicles showed a significant decrease in FA while MD, RD, and AD was increased (p<.001 for all parameters). FA of median nerve non-lesion fascicles showed a weak significant decrease compared to healthy controls (p<.01) while there was no difference in MD, RD, and AD. ROC analyses revealed an excellent diagnostic accuracy of FA, MD and RD in the discrimination of median nerve lesion and non-lesion fascicles in AINS patients as well as in the discrimination of lesion fascicles and normative median nerve values of healthy controls. - Conclusion - By applying this functional MR Neurography technique in patients with AINS, this proof of principle study demonstrates that diffusion tensor imaging is feasible to quantify structural nerve injury at the anatomical level of individual fascicles.